The larvae of caddisfly species (Insecta, Trichoptera) in northern Thai streams and their relationships to environmental variables - Seetapan, Kriengkrai; Prommi, Taeng On (Zootaxa, 2022)
There have been few systematic studies on Trichoptera larvae in Thailand. The larval stages of the endemic species remain mostly unknown. Continued work on describing the larval stages of species will improve the precision of water quality monitoring metrics and enable ecological studies of species. This paper describes the unknown larvae of Hydropsyche pallipenne Banks 1938 and Hydropsyche askalaphos Malicky & Chantaramongkol 2000, with their identities deduced from the fact that both the larvae described here and identifiable adult specimens were sampled at the same location. Also, the effects of environmental variables on the distribution of caddisfly larvae in northern Thai streams were investigated. In total, 41 taxa from seven streams were identified, representing twenty-four genera and thirteen families. The Hydropsychidae were the most numerous family collected, accounting for 1,487 specimens (54%). Trichopteran abundance (for Triaenodes sp., Marilia sumatrana, Amphipsyche meridiana, Hydropsyche askalaphos, Leptocerus sp., Ganonema sp., Chimarra cf. akkaorum, Cheumatopsyche cf. dubitans, Macrostemum sp., and Leptocerus sp.) is influenced by environmental factors such as water temperature, dissolved oxygen, total dissolved solids, ammonia nitrogen, nitrate nitrogen, and pH. Because of their significant responses to environmental fluctuations, the caddisfly assemblage proved useful in identifying variations in water quality conditions in northern Thai streams.